2022
DOI: 10.24330/ieja.1143740
|View full text |Cite
|
Sign up to set email alerts
|

Strongly EP elements and the solutions of equations in rings

Abstract: In this paper, we present many new characterizations of strongly EP elements in rings with involution. We especially investigate the strongly EP elements by constructing certain equations and considering the solutions of equations, revealing the existence of solutions of certain equations and the general solutions of some binary equations that play a role in characterizing strongly EP elements. Proofs of relevant conclusions are also given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Existing articles related to the impact of China's OFDI on host countries mainly focus on its effects on host countries' economies [18][19], income disparities [20], political stability [21], and the environments [22][23]. Despite inconsistencies, substantial studies have found that China's OFDI can promote the host countries' economic growth [24][25][26], increase the income disparity [27] and negatively affect the environment [28][29]. However, there are few empirical studies on the impact of China's OFDI on inclusive growth in host countries.…”
Section: The Impact Of China's Ofdi On Host Countriesmentioning
confidence: 99%
“…Existing articles related to the impact of China's OFDI on host countries mainly focus on its effects on host countries' economies [18][19], income disparities [20], political stability [21], and the environments [22][23]. Despite inconsistencies, substantial studies have found that China's OFDI can promote the host countries' economic growth [24][25][26], increase the income disparity [27] and negatively affect the environment [28][29]. However, there are few empirical studies on the impact of China's OFDI on inclusive growth in host countries.…”
Section: The Impact Of China's Ofdi On Host Countriesmentioning
confidence: 99%